2020
DOI: 10.1177/0003489420921424
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Laryngopharyngeal Reflux on Patient-reported Measures of Chronic Rhinosinusitis

Abstract: Objective: This study explored the impact of laryngopharyngeal reflux (LPR) on quality-of-life outcomes captured by Sino-Nasal Outcome Test (SNOT-22) and Reflux Symptom Index (RSI) in patients with chronic rhinosinusitis (CRS) and patients with symptoms of LPR. Methods: In a retrospective chart review, SNOT-22 and RSI scores were analyzed in patients seen at a tertiary care center with CRS, LPR, or both CRS and LPR. SNOT-22 items were grouped into sleep, nasal, otologic, and emotional symptom subdomains. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 49 publications
(69 reference statements)
0
31
0
Order By: Relevance
“…The included studies were published between 1999 and 2020, reporting data on a total of 22,361 patients (16,514 with rhinitis, 522 with NSD, and 5325 with CRS), with a mean age of 39.1 years (33.9 years for rhinitis, 34.0 years for NSD, and 49.3 years for CRS). Of the 103 studies, 29 reported on CRS (2 specifically excluded chronic rhinosinusitus with nasal polyps [CRSwNP], 33,34 3 did not specify CRSwNP or CRS without nasal polyps [CRSsNP], 1,15,35 and 3 specifically focused on CRSwNP, 36–38 whereas the remaining 21 studies reported varying percentages of patients with nasal polyps), 64 on rhinitis (only 3 studies included patients with NAR 39–41 ), and the remaining 10 on NSD. Studies varied in their inclusion, exclusion, and diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published between 1999 and 2020, reporting data on a total of 22,361 patients (16,514 with rhinitis, 522 with NSD, and 5325 with CRS), with a mean age of 39.1 years (33.9 years for rhinitis, 34.0 years for NSD, and 49.3 years for CRS). Of the 103 studies, 29 reported on CRS (2 specifically excluded chronic rhinosinusitus with nasal polyps [CRSwNP], 33,34 3 did not specify CRSwNP or CRS without nasal polyps [CRSsNP], 1,15,35 and 3 specifically focused on CRSwNP, 36–38 whereas the remaining 21 studies reported varying percentages of patients with nasal polyps), 64 on rhinitis (only 3 studies included patients with NAR 39–41 ), and the remaining 10 on NSD. Studies varied in their inclusion, exclusion, and diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent symptoms associated with LPR are globus sensation, throat clearing, hoarseness, excess throat mucus or postnasal drip [2,12,45]. These symptoms, which are commonly observed in primary care medicine, are nonspecific and may be associated with active laryngopharyngeal allergy [2], rhinitis [46], chronic rhinosinusitis [47], smoking [48], alcohol abuse [49], and benign laryngopharyngeal infections [50]. In other words, it is difficult to base the LPR diagnosis only on laryngopharyngeal symptoms without objective examination or exclusion of these confounding factors.…”
Section: Symptomsmentioning
confidence: 99%
“…Thus, the frequent observation of these symptoms may lead to a potential overestimation of their prevalence in LPR, which is known to be prevalent in otolaryngology [ 1 ]. Interestingly, the high prevalence of these symptoms led some authors to use the reflux symptom index (RSI) [ 19 ] as a clinical tool for the assessment of symptoms and for therapeutic outcomes in some of these conditions [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%